Meta‐analysis of associating liver partition with portal vein ligation and portal vein occlusion for two‐stage hepatectomy. Issue 13 (16th September 2016) - Eshmuminov, D.; Raptis, D. A.; Linecker, M.; Wirsching, A.; Lesurtel, M.; Clavien, P.‐A.
Abstract : Background: Discussion is ongoing regarding whether associating liver partition with portal vein ligation for staged hepatectomy (ALPPS) or portal vein occlusion is better in staged hepatectomy. The aim of this study was to compare available strategies using a two‐stage approach in extended hepatectomy. Methods: A literature search was performed in MEDLINE, Scopus, the Cochrane Library and Embase, and additional articles were identified by hand searching. Data from the international ALPPS registry were extracted. Clinical studies reporting volumetric changes, mortality, morbidity, feasibility of the second stage and tumour‐free resection margins (R0) in two‐ stage hepatectomy were included. Results: Ninety studies involving 4352 patients, including 320 from the ALPPS registry, met the inclusion criteria. Among these, nine studies (357 patients) reported on comparisons with other strategies. In the comparison of ALPPS versus portal vein embolization (PVE), ALPPS was associated with a greater increase in the future liver remnant (76 versus 37 per cent; P < 0·001) and more frequent completion of stage 2 (100 versus 77 per cent; P < 0·001). Compared with PVE, ALPPS had a trend towards higher morbidity (73 versus 59 per cent; P = 0·16) and mortality (14 versus 7 per cent; P = 0·19) after stage 2. In the non‐comparative studies, complication rates were 39 per cent in the PVE group, 47 per cent in the portal vein ligation (PVL) group and 70 per cent in the ALPPS group. After stage 2, mortality rates were 5, 7 and 12 per cent respectively. Conclusion: ALPPS is associated with greater future liver remnant hypertrophy and a higher rate of completion of stage 2, but this may be at the price of greater morbidity and mortality. Abstract : RCT investigating ALPPS is needed